(untitled) (Colombia Medica, 2024)
Introduction: The health status of caregivers is associated with satisfaction with life and so in the way of delivering care to the elderly with Alzheimer’s. Objective: To evaluate the health status and life satisfaction of family caregivers of elderly with Alzheimer’s, users of a Reference Center for Care in Alzheimer’s disease in Curitiba, Paraná, Brazil. Materials and methods: This is a cross-sectional quantitative study. The convenience sample consisted of 208 family caregivers and selected during the period December 2009 to February 2010, through the inclusion and exclusion criteria. The study was conducted in the Reference Center. Data were collected through semi-structured interviews and application of the scales: Zarit caregiver burden interview, Subjective Well-Being and Functional Staging. For statistical analysis, we applied the Chi-square, Mann-Whitney and Kruskal-Wallis test, using Epi-Info 6.04. Results were considered statistically significant if their level was less than 5% (p